Families of positive operators with reverse order - Pestil, Sebnem Yildiz (UNIV BABES-BOLYAI, 2012)
The objective of this paper is to present several invariant subspace results for collections of positive operators on Banach lattices. For any family C of positive operators in L(E), I will reverse order.
Keywords: 47B60; Mathematics